2020
DOI: 10.1002/ijc.33305
|View full text |Cite
|
Sign up to set email alerts
|

Associations of general obesity and central obesity with the risk of hepatocellular carcinoma in a Korean population: A national population‐based cohort study

Abstract: Numerous previous studies have shown an association between general obesity and hepatocellular carcinoma (HCC). However, relatively few reports on the association of central obesity and HCC are available in Asian populations. Therefore, we investigated the association between WC representing central obesity and the risk of HCC in addition to BMI representing general obesity and the risk of HCC in Korea. A total of 10 505 818 participants who received the National Health Insurance Service (NHIS) health checkups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…21 The results were similar in the study using data from South Korea. 16 Although prior studies have assessed the association of body fatness with the risk of HCC, the impact of the change in body fatness on HCC incidence has barely been investigated, with just one prospective study showing a positive association of weight gain with liver cancer risk. 24 They showed that adult weight change was related to a higher risk of HCC, independent of body weight in early adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The results were similar in the study using data from South Korea. 16 Although prior studies have assessed the association of body fatness with the risk of HCC, the impact of the change in body fatness on HCC incidence has barely been investigated, with just one prospective study showing a positive association of weight gain with liver cancer risk. 24 They showed that adult weight change was related to a higher risk of HCC, independent of body weight in early adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] However, accumulating evidence suggests that waist circumference (WC), an indicator of central fatness, is a better indicator of the metabolic disturbances that may promote HCC. [14][15][16] General and central fatness are both associated with the development of nonalcoholic fatty liver disease (NAFLD), 17 which has been hypothesized to mediate the relationship between body fatness and HCC. 18 Prior studies have focused on the association of body fatness (based on total body weight, BMI and WC) with HCC risk and HCCrelated mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies utilizing a better-defined cohort of allergic patients who are diagnosed using gold-standard methods will be needed. Since we adopted the operational definition for liver cancer from previous studies that also used NHIS database 14 , 15 , the definition of liver cancer could not be validated by registered medical records such as histological information, imaging or treatment. Thus, it can cause discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon diagnosis and death codes, we defined liver cancer events as having outpatient medical records under related diagnostic codes for more than 3 times in a year or being hospitalized for 1 or more days or death under the corresponding ICD-10 codes. In this study, the international classification of diseases 10th revision (ICD-10) codes of C22, C220, and C221 were used for overall liver cancer, HCC, and ICC, respectively, as described in previous studies 14 , 15 .…”
Section: Methodsmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the most prevalent form of primary liver cancer, which accounts for >90% of primary liver cancer cases ( Llovet et al, 2021 ). The primary risk factors for HCC include chronic viral hepatitis infection (hepatitis B or C), aflatoxin B1 intake, obesity, and excessive alcohol consumption ( Chhonker et al, 2021 ; Choi et al, 2021 ; Guan et al, 2021 ; Hwang et al, 2021 ; Lockart et al, 2021 ). These factors may be responsible for cancer-related mutations, DNA damage, and epigenetic alterations, resulting in inactivated oncogenes or inactivated tumor suppressor genes, ultimately leading to HCC development ( Rovida et al, 2015 ; Ally et al, 2017 ; Dang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%